Existence of solutions for a fractional Riemann–Stieltjes integral boundary value problem - Li, Yanfang; O’Regan, Donal; Xu, Jiafa (Nonlinear Analysis: Modelling and Control, 2024)
In this paper, we study a Riemann–Liouville-type fractional Riemann–Stieltjes integral boundary value problem under some conditions regarding the spectral radius of the relevant linear operator. The existence of nontrivial solutions is obtained using topological degree, and our results improve and generalize some results in the literature.
Keywords: Riemann–Liouville-type fractional-order differential equations; integral boundary value problems; nontrivial solutions; topological degree